2021
DOI: 10.3390/diagnostics11030451
|View full text |Cite
|
Sign up to set email alerts
|

The Role in Teledermoscopy of an Inexpensive and Easy-to-Use Smartphone Device for the Classification of Three Types of Skin Lesions Using Convolutional Neural Networks

Abstract: Background. The use of teledermatology has spread over the last years, especially during the recent SARS-Cov-2 pandemic. Teledermoscopy, an extension of teledermatology, consists of consulting dermoscopic images, also transmitted through smartphones, to remotely diagnose skin tumors or other dermatological diseases. The purpose of this work was to verify the diagnostic validity of images acquired with an inexpensive smartphone microscope (NurugoTM), employing convolutional neural networks (CNN) to classify mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Teledermatology can be classified into real-time teledermatology (VTC—live video consultation) and store-and-forward teledermatology (SAF—image transmission by the patient). Both types of teledermatology have facilitated remote dermatological assistance during the pandemic for chronic diseases and the appearance/modification of skin lesions [ 6 ]. The IDS questioned 678 of its members, from 52 different countries, about their activity during the emergency period.…”
Section: The Increased Importance Of Teledermatology Caused By Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Teledermatology can be classified into real-time teledermatology (VTC—live video consultation) and store-and-forward teledermatology (SAF—image transmission by the patient). Both types of teledermatology have facilitated remote dermatological assistance during the pandemic for chronic diseases and the appearance/modification of skin lesions [ 6 ]. The IDS questioned 678 of its members, from 52 different countries, about their activity during the emergency period.…”
Section: The Increased Importance Of Teledermatology Caused By Covid-19mentioning
confidence: 99%
“…Smartphone-based teledermoscopy, an extension of teledermatology, has improved in recent years due to the development of mobile applications and devices. Veronese et al tested an inexpensive and easy-to-use smartphone microscope device; overall, they obtained an accuracy of 83.9% for the diagnoses of skin lesions based on images acquired through the device [ 6 ]. Considering these useful tools, teledermoscopy in association with teledermatology can be used to perform the first triage of skin lesions, helping the clinician to select patients who require a face-to-face consultation [ 8 ].…”
Section: The Increased Importance Of Teledermatology Caused By Covid-19mentioning
confidence: 99%
“…In 2020, we conducted a study to verify the diagnostic reliability of images acquired through an inexpensive smartphone microscope (Nurugo TM ), employing CNNs to classify malignant melanoma (MM), melanocytic nevus (MN), and seborrheic keratosis (SK). The CNN was tested on three different test sets: (i) ISIC images, (ii) images acquired with the Nurugo TM , and (iii) images acquired with a conventional dermatoscope [ 12 ]. The Nurugo TM device showed an accuracy comparable to conventional dermatoscope (up to 80%), which demonstrates a potential role performing the first triage in TDS, selecting the skin lesions that require a face-to-face consultation with dermatologists [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CNN was tested on three different test sets: (i) ISIC images, (ii) images acquired with the Nurugo TM , and (iii) images acquired with a conventional dermatoscope [ 12 ]. The Nurugo TM device showed an accuracy comparable to conventional dermatoscope (up to 80%), which demonstrates a potential role performing the first triage in TDS, selecting the skin lesions that require a face-to-face consultation with dermatologists [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…ML models are now being used to classify dermatology clinical images in the electronic health records to optimize access to these images for research purposes ( 51 ). Furthermore, recent studies have demonstrated that dermoscopy improves the diagnostic accuracy of teledermatology ( 52 ); thus, smartphone microscope applications employing CNN are now increasingly supplementing teledermatology consults ( 53 ). Furthermore, because several dermatoses are usually initially seen by primary care providers (PCP), an AI-based tool was developed to interpret images and their associated medical histories, which improved the diagnoses of dermatoses by PCPs in a teledermatology setting ( 54 ).…”
mentioning
confidence: 99%